(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the status of hand hygiene knowledge and practices among primary school students in Tan Son Nhi Ward, Ho Chi Minh City, in 2025. Methods: A cross-sectional study was conducted among students at primary schools in Tan Son Nhi Ward, Ho Chi Minh City. Results: The study showed that students’ hand hygiene knowledge and practices were still limited. Although 58.47% of students correctly understood handwashing technique, only 34.7% knew the correct number of steps, resulting in an overall adequate knowledge rate of only 31.6%. Regarding practice, some individual behaviors had relatively high rates, such as handwashing before eating at home (90.9%), handwashing with soap (72.2%), and handwashing after touching public objects (71.8%). However, the overall adequate practice rate was only 36.1% because practice was assessed based on 8 behaviors, and only students who correctly performed at least 6 out of 8 behaviors were classified as having adequate practice. Therefore, many students performed well in some familiar behaviors but still did not meet the overall standard. In addition, students with inadequate knowledge were 1.7 times more likely to have inadequate practice than those with adequate knowledge, and this association was statistically significant (OR = 1.7; 95% CI: 1.1–2.6; p = 0.013). Conclusion: Among the 418 students surveyed, only 31.6% had adequate hand hygiene knowledge and 36.1% demonstrated appropriate handwashing practices; handwashing after toilet use at school remained especially low (36.1%). Knowledge was significantly associated with practice (OR = 1.7; p = 0.013), indicating the need to strengthen health education and improve handwashing facilities in schools.